Enzymatic Construction of Artificial Base Pairs: The Effect of Metal Shielding. (2nd September 2020) - Flamme, Marie; Levi‐Acobas, Fabienne; Hensel, Susanne; Naskar, Shuvankar; Röthlisberger, Pascal; Sarac, Ivo; Gasser, Gilles; Müller, Jens; Hollenstein, Marcel
Abstract: Th formation of metal base pairs is a versatile method for the introduction of metal cations into nucleic acids that has been used in numerous applications including the construction of metal nanowires, development of energy, charge‐transfer devices and expansion of the genetic alphabet. As an alternative, enzymatic construction of metal base pairs is an alluring strategy that grants access to longer sequences and offers the possibility of using such unnatural base pairs (UBPs) in SELEX experiments for the identification of functional nucleic acids. This method remains rather underexplored, and a better understanding of the key parameters in the design of efficient nucleotides is required. We have investigated the effect of methylation of the imidazole nucleoside (dIm n Me TP ) on the efficiency of the enzymatic construction of metal base pairs. The presence of methyl substituents on dImTP facilitates the polymerase‐driven formation of dIm 4Me −Ag I −dIm and dIm 2Me TP −Cr III −dIm base pairs. Steric factors rather than the basicity of the imidazole nucleobase appear to govern the enzymatic formation of such metal base pairs. We also demonstrate the compatibility of other metal cations rarely considered in the construction of artificial metal bases by enzymatic DNA synthesis under both primer extension reaction and PCR conditions. These findings open up new directions for the design of nucleotide analogues for the development of metal base pairs. Abstract : A, C, G, T… Ag, Cr : We have explored using nucleotides bearing methylated imidazole base surrogates to expand the genetic alphabet with artificial metal base pairs. This methylation pattern improves silver‐mediated base pair formation compared to the unmodified imidiazole nucleotide. We extended this approach to underexplored metal ions and observed the formation of a chromium‐mediated metal base pair.